From 'Entering into a Firm' to 'Entering into a Profession': An Anthropological Approach to Changing Personhood in Japan. (14th September 2015) - Fu, Huiyan
Abstract: Drawing on extensive ethnographic fieldwork, the article uses discourse analysis to examine the social dynamics involved in the construction of personhood in Japan. While the gap between powerful discourse and lived reality is a well‐documented phenomenon, there is little systematic empirical research on how to integrate individual and social levels of analysis in this process. By contrasting discourse from above and from below, the article illuminates power asymmetry and the resulting tension between discursive freedom and social exclusion among disadvantaged groups.